Fruit Tree (Malus domestica) Branch Biochar via Pyrolysis: Optimization of Temperature and Holding Time - Zhao Cao; Yujia Li; Xinran Xie; Huadong Zhang; Shoujun Yang (BioResources)
Discarded apple tree branches from Yantai, China, were pyrolyzed at 300 to 700 °C with holding times (0 to 120 min) to optimize biochar production parameters. Results showed that compared to 300 °C, increasing pyrolysis temperature from 400 to 700 °C (0 min holding) enhanced fixed carbon content 1.39 to 8.30%, carbon content by 16.31 to 28.84%, while reducing C/H ratios 18.29 to 66.33%. When holding time extended from 60 to 120 min across temperatures, fixed carbon content increased 0.31 to 2.56% below 600 °C but showed minimal gains at higher temperatures. Carbon content changes became negligible (≤ 0.69%) above 500 °C with extended holding. Considering both quality and yield, 600 °C pyrolysis temperature with 60 min holding time was identified as the optimal condition for producing biochar with enhanced carbon stability and resource utilization efficiency. This study provided scientific support for converting fruit tree waste into functional carbon materials through controlled pyrolysis processes.